Dietary Intervention Associated With Moderate-Intensity Continuous Training Leads to Changes in the Inflammatory Profile in Visceral Adipose Tissue but Not in Skeletal Muscle in Diet-Induced Obese Rats - Costa, Jean Lucas Fernandes da; Furino, Vanessa de Oliveira; de Castro, Cynthia Aparecida; Alves, João Manoel; Duarte, Ana Cláudia Garcia de Oliveira (Frontiers in Physiology, 2022)
This study aimed to determine concentrations of inflammatory markers in visceral adipose tissue and skeletal muscle, changes in body mass and adipocyte size in diet-induced obese rats after moderate-intensity continuous training (MICT) and/or dietary intervention. After eight weeks of obesity induction through high-fat diet (HFD) consumption, twenty diet-induced obese male Wistar rats were divided into four groups: (i) control rats fed with HFD (HFD-SED), (ii) obesity rats fed with HFD and submitted to MICT (HFD-MICT), (iii) obesity rats that were submitted to a nutritional intervention by switching HFD to chow diet (CD-SED), and (iv) obesity rats that were submitted to MICT and nutritional intervention (CD-MICT). All the animals in the training groups were submitted to MICT, with an intensity of 50-85% of Vmax, 60min/day, 3 days/week for 8 weeks. Gastrocnemius (GAST) and mesenteric adipose tissue (mWAT) were collected to quantify TNF-α, IL-6 and IL-10 through Enzyme-Linked Immunosorbent Assay (ELISA). The body mass was recorded before and after the experimental protocols and the adipocyte morphology was assessed using histological analysis. The results showed that HFD-SED had higher body mass, higher concentrations of inflammatory markers in mWAT and an increase in adipocyte size. The CD-SED and CD-MICT groups presented reduced body mass, relative weight of mWAT, and adipocyte size. Moreover, the inflammatory markers in mWAT were reduced after dietary intervention (TNF-α), MICT (IL-10 and TNF-α) or both interventions combined (IL-6 and TNF-α). On the other hand, there was no reduction in GAST relative weight or concentrations of inflammatory markers for any treatment. Finally, we concluded that eight weeks of dietary intervention alone and combined with MICT were effective in reducing some of the deleterious effects caused by obesity.